2018
DOI: 10.1155/2018/7891748
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Three Echinoderm Species as New Opportunity for Drug Discovery: Their Bioactivities and Antimicrobial Properties

Abstract: Echinoderms are a renewable resource with an economic value due to their increasing demand as food and/or source of bioactive molecules exerting antitumor, antiviral, anticoagulant, antioxidant, and antimicrobial activities. In this framework, the present study is aimed at investigating the antibacterial, antioxidant, and hemolytic activities in the three Echinoderm species Echinaster sepositus, Arbacia lixula, and Sphaerechinus granularis. The sea star E. sepositus showed lysozyme-like activity (mean diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…Lysozyme-like activity was evaluated by using inoculated Petri dishes as standard assay [73]. Briefly, 700 mL of 5 mg/mL of dried M. luteus cell walls (Sigma) was diluted in 7 mL of 0.05 M PB-agarose (1.2%) (pH 5.2) and then spread on a Petri dish.…”
Section: Methodsmentioning
confidence: 99%
“…Lysozyme-like activity was evaluated by using inoculated Petri dishes as standard assay [73]. Briefly, 700 mL of 5 mg/mL of dried M. luteus cell walls (Sigma) was diluted in 7 mL of 0.05 M PB-agarose (1.2%) (pH 5.2) and then spread on a Petri dish.…”
Section: Methodsmentioning
confidence: 99%
“…In the phylum Echinodermata, the analyzed species showed the same antibiotic activity than other Echinodermata species reported in the literature such as Strongylocentrotus droebachiensis, Asterias rubens, Cucumaria frondosa and Diadema setosum (Haug et al, 2011;Marimuthu et al, 2015). These extracts could contain antimicrobial peptides or saponins because both are easily extracted with organic solvents (Andersson et al, 1989;Li et al, 2008) and are produced by coelomocytes cells or tissue specific cells as part of their immune response against pathogens (Haug et al, 2011;Li et al, 2015;Coates et al, 2018;Nalini et al, 2018;Stabili et al, 2018). The coelomic cells of Loxechinus albus are reported as a producer of antibiotic substances activity against Escherichia coli (Pizarro et al, 2012), and this study is adding more sources of antibiotic substances in the same species.…”
Section: Echinodermatamentioning
confidence: 95%
“…3). The echinoderm species widespread in the Mediterranean area such as Echinaster sepositus, Sphaerechinus granularis, and Arbacia lixula are reported to be potential source of antioxidant compounds (Stabili et al 2018). Dakrory et al (2015) reported that extract of sea cucumber Holothuria atra displayed free radical scavenging properties and in-vivo antioxidant activity in animal models.…”
Section: Antioxidant Activitymentioning
confidence: 99%